An analysis of citation and research trends of Bachelor of Library and Information Science (BLIS) Theses 1996-2004 - Villanueva, Michael V. (Institute of Library and Information Science, University of the Philippines Diliman, 2005)
Two hundred ninety-two undergraduate theses submitted to the UPILIS during the period of 1996-2004 were analyzed to determine the present trends in research in the field of Library and Information Science (LIS) and to help in collection development and maintenance of the Institute's Library. Citation analysis was utilized to determine the characteristics of the source materials; subject analysis was done to find out the most commonly researched area and used research methodology. Descriptive statistics such as frequency and percentages were used in the analysis.